Selection for bean yield under low and high stress environments - Singh, S.P.; Cajiao V., César Hernando; Gutiérrez, J.A.; García, J.; Pastor Corrales, Marcial A.; Morales, Francisco José (1988)
A selection study was conducted with 6 hybrid bean populations in 3 double groups, with low, intermediate, and high yield potential, at CIAT`s exptl. farm in Popayan (Cauca, Colombia), in a P-deficient soil with pH 4.5. These soil conditions allow for high disease incidence such as anthracnose (Colletotrichum lindemuthianum). Two management levels were implemented, namely the addition of lime and fertilizers and anthracnose stress, to create high and low stress environments. A total of 6 lines with high yield and resistance to BCMV were found in all stressed environments; 72 lines were obtained by selection (visual and mass selection), from the F2 to the F6 generations, which were evaluated during 3 yr with the high yielding and BCMV-resistant parents as well as with 4 other model checks. Selection for seed yield is effective in both types of environments, although differences in line performance in both environments were not significant. The highest yielding lines were always obtained from the highest yielding parents, despite the selection environment. Highest yielding crosses were obtained by crossing small-seeded germplasm from low lands with medium-seeded wild forms from the Central American highlands. (CIAT)